LOS PESCADORES Y AGRICULTORES DE LA COSTA DE NAYARIT FRENTE A LA GOBERNANZA DE LOS RECURSOS COMUNES. EL CASO DE BOCA DEL ASADERO Y LAURELES Y GÓNGORA (EL LIMÓN), MÉXICO - Rodríguez Domínguez, Elida Leticia (2017)
This article identifies the organizational strategies and innovations of Boca del Asadero and Laureles y Góngora (El Limón), two agricultural and fishing communities from Nayarit that faced a growing loss of control of their natural resources. The strong changes in social and productive management of this communities are part of the process of modernization associated to the implementation of transnational type of neoliberal policies promoted by the Mexican state since the second half of the 20th century, as arethe constructions like the hydroelectric dam of Aguamilpa and the installation of the aqua cultural company, Aquanova. Two approaches were applied: quantitative and qualitative; in the first one, a poll was taken in the modality of interview of census type to all homes and in the second, interviews with depth were made with key actors. The results show a scenario of the individualization of the common interests and of the conflicts that derive from the system of the management of the natural resources, etc.